The aspect of ease in the life of Holy Prophet (SAW) and its application on modern times (A Research study in the light of Seerat e Tayyaba): مزاج نبویﷺ کا تیسیری پہلو اور عصر حاضر میں اس سے استفادہ (سیرت طیبہ کی روشنی میں تحقیقی مطالعہ) - Rehman, Dr. Syed Mujeeb Ur (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Man performs various matters of daily life under the influence of his feelings and emotions. Some people have hardness in their temperament. This hardness is reflected in their every work. Rasool Ullah (SAW) is sent as Rahmah for humanity. Creating easiness(yusr) for others is a dominant factor in his personality . Therefore, he created easiness for the Ummah at every point of life, including making laws, explaining Hukm e Shar’i and deciding between people. There is an element of harshness in the mood of people nowadays, due to which they cause hardship to others in various matters of life. Teachers, religious scholars and leaders have an important role in the construction and destruction of the society. If these important sections of society develop aspect of easiness in their temprament, there will be positive effects on the society. This article has been written to highlight the aspect of easiness in the life of the Holy Prophet(SAW). It explains that this aspect was dominant in every phase of the Prophet’s life. It also points out the practical ways that can be followed to make things easier for others in the present era.